The importance of non-formal education for positive socialization - SKIRMANTIENĖ, Jolanta (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryRecently, numerous discussions about the importance of informal teaching in Lithuania have emerged. Nonetheless, various researches and the practical situation reveal the poor variety of out-of-class activities for children and provides for non-formal teaching activities that dissatisfy schoolchildren needs. The objectives of this research were to disclose the theoretical background of the non-formal teaching in the positive socialization, to determine what are the exact preconditions of a successful establishment of the nonformal teaching process for children, and to point out the improvement possibilities of non-formal teaching. Scholars emphasize the importance of non-formal teaching for creativeness and the important activities that influence the values and a positive socialization of a person. To organize qualitative leisure time activities of children and their motivation, participation are essential pedagogical issues in Lithuania and other countries. The objective of the present research was to expose the importance of non-formal education for the positive socialization of children.The conclusion of the research:When speaking about the conception of non-formal education, it is important to acknowledge that the informal teaching is oriented on the development of professional skills and improving personality. The nonformal education provides a young person with a possibility of expressing himself in a field where he or she is capable to improve individual potency, find appealing ways of spending leisure time, to acquire new competencies.The examined references and the undertaken study revealed that positive personality establishment is highly influenced by family, the culture of school, the informal peer, (the pattern) of adults and friends behaviour, where the informal education takes a place in such formation too. Well organized informal teaching of children and teenagers is an essential condition for socialization of a new peer and most effective crime prevention.– Both parties of respondents (herein, teachers and parents) equally agree on a fact that the process o informal teaching positively influences a child’s personality development. The majority of the respondents confirm that during participation in the informal teaching process, social, personal and educational competencies are developed.– Questioned parents and teachers approve that during the participation in such informal teaching activities such students’ (children) capabilities as self-sufficiency, self-confidence, responsibility and attentiveness are developed. According to the opinion of the respondents, the activity of informal teaching fosters their busyness, motivates them to take a part in their favourite activity, helps pupils to positively socialize in a society and expose children personal skills.– Concerning the problems arisen in the informal teaching, both parties claimed there is shortage of kids’ clubs, they also mentioned the financing difficulties and deficiency of desirable kids’ clubs.Key words: non-formal education, non-formal education of children, positive socialization.